2016
DOI: 10.1371/journal.pone.0163919
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Permeases and Virulence in Cryptococcus neoformans

Abstract: Fungal opportunistic pathogens colonize various environments, from plants and wood to human and animal tissue. Regarding human pathogens, one great challenge during contrasting niche occupation is the adaptation to different conditions, such as temperature, osmolarity, salinity, pressure, oxidative stress and nutritional availability, which may constitute sources of stress that need to be tolerated and overcome. As an opportunistic pathogen, C. neoformans faces exactly these situations during the transition fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 73 publications
6
54
1
Order By: Relevance
“…CaGap1-6 -CnAap1-8 oap4△/oap5△, oap1△/aap2△ and oap8△ strains are attenuated in G. melonella model, aap4△/aap5△ in murine inhalation model [34,35] AfGap1 -CaTor1 has not been studied in detail, it is assumed that it likewise influences the expression of NCR-associated genes and amino acid permeases (AAPs) [43], while Aftor was shown to be involved in amino acid metabolism [44]. The nitrogen or amino acid metabolism-related functions of CnTor1 have not been defined.…”
Section: Scgap1mentioning
confidence: 95%
“…CaGap1-6 -CnAap1-8 oap4△/oap5△, oap1△/aap2△ and oap8△ strains are attenuated in G. melonella model, aap4△/aap5△ in murine inhalation model [34,35] AfGap1 -CaTor1 has not been studied in detail, it is assumed that it likewise influences the expression of NCR-associated genes and amino acid permeases (AAPs) [43], while Aftor was shown to be involved in amino acid metabolism [44]. The nitrogen or amino acid metabolism-related functions of CnTor1 have not been defined.…”
Section: Scgap1mentioning
confidence: 95%
“…Amino acids and the acquisition of nitrogen are important for virulence in C. neoformans (21,(37)(38)(39)(40), and amino acids differed in their support of growth as sole nitrogen sources. We found that the WT strain and the atgΔ mutants of C. neoformans were able to grow equally well when transferred from a rich medium (YPD) to media with preferred amino acids, presumably because the cells were induced for uptake and use of the amino acids.…”
Section: Fig 10mentioning
confidence: 99%
“…Notably, amino acid permeases are important for the protection of the yeast when challenged by environmental or host promoted stress conditions. C. neoformans mutants with defect in these enzymes are less virulence, highlighting the importance of amino acid uptake during infection [85]. Yeast cells deficient in a small protein allegedly involved in the citric acid cycle had a higher expression of amino acids (i.e.…”
Section: Discussionmentioning
confidence: 99%